Cutaneous and Mucosal Lichen Planus: A Comprehensive Review of Clinical Subtypes, Risk Factors, Diagnosis, and Prognosis. (30th January 2014) - Gorouhi, Farzam; Davari, Parastoo; Fazel, Nasim
Abstract : Lichen planus (LP) is a chronic inflammatory disorder that most often affects middle-aged adults. LP can involve the skin or mucous membranes including the oral, vulvovaginal, esophageal, laryngeal, and conjunctival mucosa. It has different variants based on the morphology of the lesions and the site of involvement. The literature suggests that certain presentations of the disease such as esophageal or ophthalmological involvement are underdiagnosed. The burden of the disease is higher in some variants including hypertrophic LP and erosive oral LP, which may have a more chronic pattern. LP can significantly affect the quality of life of patients as well. Drugs or contact allergens can cause lichenoid reactions as the main differential diagnosis of LP. LP is a T-cell mediated immunologic disease but the responsible antigen remains unidentified. In this paper, we review the history, epidemiology, and clinical subtypes of LP. We also review the histopathologic aspects of the disease, differential diagnoses, immunopathogenesis, and the clinical and genetic correlations.